Aromatase changes in depression: A postmortem and animal experimental study. (March 2017) - Wu, Juan-Li; He, Yang; Hrubý, Radovan; Balesar, Rawien; Qi, Yang-Jian; Guo, Lei; Ren, Zhong; Zhu, Qiong-Bin; Huang, Man-Li; Swaab, Dick F.; Bao, Ai-Min
Highlights: Depression is characterized by a hyperactive hypothalamo-pituitary-adrenal (HPA) axis. Increased aromatase was hypothesized for explaining sex-steroid-dependent HPA activation. However, decreased hypothalamic aromatase expression was observed in major depression. Aromatase inhibitor administration did not change depression-symptoms in a rat model. Aromatase changes in adulthood do not play a key role in the symptoms of depression. Abstract: A hyperactive hypothalamo-pituitary-adrenal (HPA) axis is a prominent feature in depression. It has been shown that androgens inhibit HPA activity and that estrogens stimulate it. We have therefore investigated, in human postmortem hypothalamus, whether depression features an increase in aromatase, which is the rate-limiting enzyme for the conversion of androgens to estrogens. In addition, we have tested the effect of an aromatase inhibitor on depression-like symptoms in a frequently used animal model for depression. At first, aromatase immunoreactivity (ir) was quantified in the central part of the hypothalamic paraventricular nucleus (PVN) of 10 major depressive disorder (MDD) patients and 10 well-matched control subjects. Subsequently an animal experimental study was performed using the chronic unpredictable mild stress (CUMS) rats as depression model. The effect of administration of 1, 4, 6-androstatriene-3, 17-dione (ATD), an aromatase inhibitor, was investigated by silastic capsule implantation. In the postmortem study, the amount of PVN aromatase-ir decreased significantly in the MDD group compared to the controls (P = 0.029). In the animal study, ATD was found to cause significantly increased testosterone (T) levels, both in plasma and in the hypothalamus. However, ATD administration did not show significant effects on the depression-like behaviors or plasma corticosterone levels in CUMS rats. Based on our observations in human postmortem material and the animal experiment, we have to conclude that alterations in aromatase in adulthood do not seem to play a major role in the pathogenesis of the symptoms of depression.